The Integrative Thematic Model with HAJRAH Syntax on Children's Peace Culture Value in Early Childhood Education in Makassar, Indonesia. - Hajerah, Hajerah; Herlina , Herlina; Rusmayadi , Rusmayadi; Ilyas, Sitti Nurhidayah; Amri, Nur Alim; Amri, Nurzil (JURNAL PENDIDIKAN USIA DINI, 2026)
Early childhood is a critical phase for cultivating character and social values, including peaceful coexistence. This study aims to examine the effectiveness of the integrative thematic learning model with HAJRAH syntax (High Preparation, Action, Joining, Reaction, Assessment, High Reinforcement) in developing peace culture values in young children. Using a quasi-experimental design with a non-equivalent control group, 26 kindergarten children (aged 5–6) in Makassar were divided into experimental and control groups. Data were collected using a pre-test and post-test questionnaire and observation sheet validated by experts (CVI = 0.87; Cronbach's α = 0.81). The independent sample t-test revealed a significant difference between the groups (p < 0.001), with the experimental group showing a mean increase of 2.636 points in peace culture indicators (tolerance, cooperation, conflict resolution). The findings indicate that HAJRAH-based learning fosters stronger social-emotional development and peaceful behaviors in children. This model offers a promising pedagogical framework for implementing character education in early childhood settings.